(untitled) (مجلة أبحاث قانونية, 2023)
International crimes derive their definitions from multiple and diverse documents and instruments, which the legislator - any legislator - can be guided by and benefit from when including international crimes in criminal law as references for this inclusion, in order to gain a largely complete legislative experience. However, the multiplicity and diversity of these references raises the question about what are the most important references that can be referred to, and whether they are of a binding nature for the Libyan state or not, after the inclusion of international crimes in the Libyan criminal law has become an existing possibility according to the text of Article (36) of The draft Libyan constitution for the year 2017. To answer the question raised, the research studied a number of international and regional referencesthe relevant contain, and concluded with several results, the most important of which is that the international agreements in force are considered the most important references in the field of defining international crimes. Because it includes most international crimes, and they are of a binding nature for the Libyan state. It is a state party to a large number of them, and most other references base their definition of international crimes on these conventions.